On-line Consumer Behavior: the flow theory perspective - Farias, Salomão Alencar de; Kovacs, Michelle Helena; Silva, Janaynna Menezes da (Review of Business Management, 2008)
This article investigates the on-line consumer behavior based on the flow theory, defined as the holistic sensation that people feel when acting with total involvement in an activity (CSIKSZENTMIHALYI, 1975). This theory has been used for better understanding the purchase behavior through the Internet, although this concept is still not sufficiently clear in consumer behavior literature, since it does not exist a consensus regarding which factors that precede, characterize or are consequences of the flow state. Thus, the present research was aimed at identifying the constructs related to the flow state that must be part of an on-line purchase behavior framework, indicating which is its applicableness for achieving consumer satisfaction in the purchase by the Internet. It was used a descriptive methodology with the application of a survey to a sample of 237 electronic retail consumers. Collected data was analyzed by means of multivariate statistical techniques and results indicated that the on-line environment and the telepresence precede the flow, that in turn is associated to the exploratory behavior, positive effect of the navigation process, purchase and satisfaction with the purchase process. Key-words: Flow. Internet. Purchase behavior. Telepresence. Store environment.